Evaluation of the reach and impact of the 100% Jeune youth social marketing program in Cameroon: findings from three cross-sectional surveys - Plautz Andrea; Meekers Dominique (BMC, 2007)
Abstract Background The 100% Jeune youth social marketing program in Cameroon aims to address the high STI/HIV prevalence rates and the high levels of unwanted pregnancy. This study evaluates the 100% Jeune program, analyzing its reach and impact on condom use, level of sexual activity, and predictors of condom use. Methods This analysis uses data from three waves of the Cameroon Adolescent Reproductive Health Survey, implemented at 18-month intervals between 2000 and 2003. The sample is restricted to unmarried youth aged 15-24; sample sizes are 1,956 youth in 2000, 3,237 in 2002, and 3,370 in 2003. Logistic regression analyses determine trends in reproductive health behavior and their predictors, as well as estimate the effect of program exposure on these variables. All regression analyses control for differences in sample characteristics. Results A comparison of trends over the 36-month study period shows that substantial positive changes occurred among youth. Results of dose response analyses indicate that some of these positive changes in condom use and predictors of use can be attributed to the 100% Jeune youth social marketing program. The program contributed to substantial increases in condom use, including consistent use with regular partners among youth of both sexes. Among males, it also contributed to consistent use with casual partners. While condom use increased with both regular and casual partners, levels of use are higher with the latter. Observed secular trends indicate that factors besides the 100% Jeune program also contributed to the observed improvements. Despite efforts to promote abstinence, the 100% Jeune program had no effect on levels of sexual activity or number of sexual partners. Likewise, there is no evidence that reproductive health programs for youth lead to increased sexual activity. Conclusion Results show that 100% Jeune successfully used a variety of mass media and interpersonal communication channels to reach a high proportion of youth throughout the intervention period. In a context in which a variety of governmental and nongovernmental partners are increasing youth-focused reproductive health programming, the 100% Jeune program reached a higher proportion of youth than did other programs. Collective efforts of multiple organizations over time can lead to improvements in adolescent reproductive health. Resources should be allocated to identify and understand predictors of abstinence and partner reduction to inform future programming decisions.